126 A case report of the emergence of neurosarcoidosis after COVID-19 infection. Issue 6 (27th May 2022) - Robinson, Rebecca; Nelson, Adam; Hughes, Stella; Kinney, Michael
Abstract : Introduction: Sarcoidosis is a granulomatous disease with protean manifestations. The aetiology is not fully understood. Infectious agents are considered to potentially contribute to its pathogenesis. This case report highlights the emergence of neurosarcoidosis after COVID-19 infection. Case: A 48 year old female developed cough, myalgia and fatigue and was diagnosed with COVID-19 based on serological testing in April 2020. Post-infection, she developed a reactive arthritis, then presented in June with left facial lower motor neuron weakness, initially treated as a Bell's palsy with a significant neuralgic component. This pain resolved with steroid treatment. One month later she developed multiple cranial neuropathies and bilateral leg weakness. MRI brain showed bilateral enhancement of the trigeminal and facial nerves. CSF was abnormal (CSF protein 0.95g/L, WCC 9/uL). Leg power rapidly improved with intravenous immunoglobulins, and FDG-PET identified mediastinal and axillary hilar lymphadenopathy. A neck node showed non-necrotising granulomatous inflammation. CSF angiotensin converting enzyme was elevated (2.07umol/min/L). She has since commenced high dose steroids for probable neurosarcoidosis. Discussion: This case suggests a possible association between COVID-19 and the emergence of sarcoidosis. At present the strength of any association is uncertain and putative mechanisms remain to be determined. rrobinson17@qub.ac.uk 88